Improving the accuracy of biologically effective dose (BED) estimates, from a previously published study, after radiosurgery for acoustic neuromas - Hopewell, JW; Moore, J; Villafuerte, CJ; Paddick, I; Jones, B; Hill, MA; Tsang, DS (Elsevier, 2022)
Objective To recalculate biological effective dose values (BED) for radio-surgical treatments of acoustic neuroma from a previous study. BEDs values were previously overestimated by only using beam-on times in calculations, so excluding the important beam-off-times (when deoxyribonucleic acid repair continues) which contribute to the overall treatment time. Simple BED estimations using a mono-exponential approximation may not always be appropriate but if used should include overall treatment time.